The Acari Hypothesis, V: deciphering allergenicity - Retzinger, Andrew C.; Retzinger, Gregory S. (Frontiers in Allergy, 2024)
The Acari Hypothesis posits that acarians, i.e., mites and ticks, are operative agents of allergy. It derived from observations that allergens are molecular elements of acarians or acarian foodstuffs. A corollary of The Hypothesis provides how acarian dietary elements are selected as allergens; namely, a pattern recognition receptor native to the acarian digestive tract complexes with dietary molecules problematic to the acarian. By virtue of its interspecies operability, the receptor then enables not only removal of the dietary elements by the acarian immune system, but also—should such a complex be inoculated into a human—production of an element-specific IgE. Because pattern recognition receptors bind to molecules problematic to the organism from which the receptors originate, it follows that molecules targeted by adaptive IgE, i.e., allergens, must be problematic to acarians. This claim is supported by evidence that host organisms, when infested by acarians, upregulate representative members of allergenic molecular families. Appreciation of the relationship between allergens and acarians provides insight well beyond allergy, shedding light also on the anti-acarian defenses of many living things, especially humans.